2015
DOI: 10.1128/jvi.02570-14
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput RNA Sequencing-Based Virome Analysis of 50 Lymphoma Cell Lines from the Cancer Cell Line Encyclopedia Project

Abstract: Using high-throughput RNA sequencing data from 50 common lymphoma cell culture models from the Cancer Cell Line Encyclopedia project, we performed an unbiased global interrogation for the presence of a panel of 740 viruses and strains known to infect human and other mammalian cells. This led to the findings of previously identified infections by Epstein-Barr virus (EBV), Kaposi's sarcoma herpesvirus (KSHV), and human T-lymphotropic virus type 1 (HTLV-1). In addition, we also found a previously unreported infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 56 publications
6
61
1
Order By: Relevance
“…6A). These data are in good agreement with the previously published splicing analyses performed using EBV gastric carcinoma tumors and EBV-infected lymphocytes, suggesting that the splicing pattern of the BARTs is relatively constant during EBV latency (13,28). These data suggest that the cDNA clone that was generated from the C15 tumor is also expressed in AGS-EBV cells, although it is not the most abundant isoform.…”
Section: Resultssupporting
confidence: 82%
“…6A). These data are in good agreement with the previously published splicing analyses performed using EBV gastric carcinoma tumors and EBV-infected lymphocytes, suggesting that the splicing pattern of the BARTs is relatively constant during EBV latency (13,28). These data suggest that the cDNA clone that was generated from the C15 tumor is also expressed in AGS-EBV cells, although it is not the most abundant isoform.…”
Section: Resultssupporting
confidence: 82%
“…To investigate this issue further, we first performed a global virome analysis on the expanded cohort of patient GC RNA-seq (n ϭ 285) and whole-exome sequence (WXS) (n ϭ 352) data sets from TCGA (8), using a directed virome analysis approach that we have reported previously (9,10). For this analysis, all RNA-seq and WXS data sets were aligned to an index containing the human genome (Genome Reference Consortium GRCh37) plus 740 mammalian viral genomes, using the transcript aligner STAR (Spliced Transcripts Alignment to a Reference) (11) run with default options plus the clip5pNbases 6 and outFilterMultimapNmax 1000 command options (removes the first 6 bases of each read and filters out any reads that map to more than 1,000 regions of the genome, respectively).…”
mentioning
confidence: 99%
“…The EBVtransformed cell line Raji is a well-described B cell line with substantial growth potential. DNA analyses revealed that Raji cells have an integrated copy of EBV in intron 1 of BACH2, and transcriptome analyses detected a loss of BACH2 expression in this cell line (112,113). Reintroduction of BACH2 expression in these cells results in a loss of clonogenic activity (114), suggesting downregulation of BACH2 facilitated persistence, clonal expansion, or both.…”
Section: Integration Site: a Determining Factor In Viral Pathogenesismentioning
confidence: 99%